2016
DOI: 10.1111/inr.12272
|View full text |Cite
|
Sign up to set email alerts
|

The perspectives of preceptors regarding clinical assessment for undergraduate nursing students

Abstract: The themes that emerged from the focus group discussions could assist in the development of a more reliable and valid clinical assessment tool to evaluate the clinical competence of nursing students in transition to practice. Clinical and educational institutions could collaborate closely to develop an educational programme and a preceptorship handbook, focusing on pedagogical contents for clinical education and assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 36 publications
0
29
0
1
Order By: Relevance
“…Due to this, many mentors consider the mentorship as stressful work, associated to multiple functions, which are not altogether clear. (21,26) This was also described in this study, in the category of "responsibility in front of the patient and the health staff", where mentors need to be present, directly supervise the student assigned to them, given that a medication error can have serious consequences, which is why mentors need to know their intern well. They must create a relationship based on trust and honesty, given that only under those terms, can mentors advance and feel secure with student formation.…”
Section: Big Responsibilitymentioning
confidence: 75%
See 2 more Smart Citations
“…Due to this, many mentors consider the mentorship as stressful work, associated to multiple functions, which are not altogether clear. (21,26) This was also described in this study, in the category of "responsibility in front of the patient and the health staff", where mentors need to be present, directly supervise the student assigned to them, given that a medication error can have serious consequences, which is why mentors need to know their intern well. They must create a relationship based on trust and honesty, given that only under those terms, can mentors advance and feel secure with student formation.…”
Section: Big Responsibilitymentioning
confidence: 75%
“…(20,21) Per se, being mentors to students generates satisfaction, especially if they feel they are prepared as educators, and clarity with exercising the role. (13,21,22) Vocation and gratification are the starting point to create respectful, amiable, and collaborative relationships with the students, conditions studied as preponderant when conducting successful mentorships. (23) In the Chilean study, the category "being there in the relationship with the students" is perceived as "a personal and professional commitment resulting in possibilities for both".…”
Section: Vocation and Gratificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In prior studies, preceptors have reported that they often have difficulty understanding the assessment tool and, therefore, interpret it differently (Wu et al , ). Students also shared that preceptors had different expectations about their performance and varied in their grading (Wu et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Nursing students, preceptors, CNLs, and academics play important roles in clinical assessment. While the students' and preceptors' perspectives are reported elsewhere, this paper reports the perspectives of CNLs and academics on clinical assessment (Wu et al , , ).…”
Section: Introductionmentioning
confidence: 99%